Association among dietary magnesium, serum magnesium, and diabetes: a cross-sectional study in middle-aged and older adults. Issue 1 (December 2016) - Wei, Jie; Zeng, Chao; Li, Xiao-xiao; Gong, Qian-yi; Lei, Guang-hua; Yang, Tu-bao
Abstract Background A number of studies have reported the association between magnesium (Mg) and diabetes. However, the various conclusions were inconsistent and the data on the Chinese population was limited. The objective of this study was to evaluate the association among dietary Mg, serum Mg, and diabetes in Chinese adults. Methods A cross-sectional study that contained 2904 subjects was conducted. Biochemical test results and dietary intakes of subjects were collected for analysis. The adjusted odds ratios (ORs) and the corresponding 95 % confidence intervals (95 % CIs) were used to determine the relationship between Mg status and diabetes by logistic regression. Results The prevalence of diabetes of the investigated population was 10.1 %. Dietary Mg intake was not significantly correlated with diabetes (P > 0.05). The significant negative association between serum Mg and diabetes existed, and the multivariate adjusted OR was 0.34 (95 % CI 0.24, 0.49) in model 3 for the highest quartile of serum Mg compared with the lowest. TheP values for trend were all less than 0.001 for the relationship between serum Mg and diabetes. Dietary Mg intake and serum Mg were not significantly correlated in the diabetes population (P = 0.936). Conclusions Dietary Mg was not significantly correlated with diabetes, while serum Mg was inversely correlated with diabetes in the Chinese population. Meanwhile, dietary Mg intake and serum Mg were not significantly correlated in the diabetes population.